indonesia: Indonesia - Aditia, Donny; Dwihantoro, Andi (Lietuvos chirurgija, 2023)
Background. Omental cysts are rare intra-abdominal tumors in children. It is challenging to diagnose since other big abdominal cysts are difficult to distinguish from in clinical and CT imaging. Aim. This case report aims to accurately and thoroughly determine the diagnosis based on the anamnesis, clinical and imaging examinations to choose the best treatment for the patient. Case Report. A 4-year-old girl reported having an enlarged belly in the past two months; the anamnesis provided the diagnosis. A mobile, 15 cm by 15 cm mass with dull percussion was discovered during clinical investigations in the top border. It was determined by anamnesis, physical examination, and imaging that the diagnosis was an ovarian cyst. Instead of an ovarian cyst, we found an omental cyst during the operation, thus we had to conduct an excision and omentectomy and postoperatively achieved favorable results. She was discharged three day after. Discussion. An abdominal CT scan showed an ovarian cyst. In laparotomy, we found a giant omental cyst, not originating from the ovaries, and did an omentectomy to excision the cyst. CT scan shows that the giant abdominal cyst is difficult to distinguish between omental, mesenteric, and ovarian cysts. Precise identification of stomach cysts is necessary. Also, doctors need to read the CT scan image more carefully. Conclusion. Giant omentum cysts are difficult to distinguish clinically and imaging from ovarian and mesenteric cysts. There is a need for a more detailed history, physical examination, and support, as well as a more thorough reading of the CT scan.